Cereal rye biomass effects on giant ragweed suppression inform management decisions - Guilherme Chudzik; Jose J. Nunes; Nicholas J. Arneson; David E. Stoltenberg; Rodrigo Werle (Agrosystems, Geosciences & Environment)
Abstract Giant ragweed (Ambrosia trifida L.) has become one of the most troublesome weeds across the US Midwest partially due to its early emergence, high competitiveness, and herbicide resistance evolution. This study aimed to determine the amount of cereal rye (Secale cereale L.) biomass needed to suppress giant ragweed establishment and growth. The study was conducted in 2022 and 2023 at the Rock County Farm near Janesville, WI, in naturally infested giant ragweed fields. At establishment, the research site was tilled to remove weed biomass and crop residue, followed by placement of eight cereal rye biomass treatments: 0, 0.6, 1.2, 2.4, 4.8, 7.2, 9.6, and 12.0 Mg ha−1. Cereal rye biomass was collected from a fall‐seeded cover‐cropped field, oven‐dried until constant mass, and evenly spread on the surface of each plot based on respective rates. Data were collected 42 days after study establishment, consisting of giant ragweed plant height, density, and dry biomass. Results showed that 3.8 and 4.8 Mg ha−1 of cereal rye biomass reduced giant ragweed biomass and density by 50%, respectively, compared to the no‐biomass treatment. Maximum giant ragweed height reduction in this study was 40% compared to the no‐biomass treatment. Our results show that cereal rye cover crop biomass was effective in suppressing giant ragweed establishment and growth with a minimum of 3.8 Mg ha−1 cereal rye biomass for >50% suppression of giant ragweed establishment and growth. These results quantify the relationship between cereal rye dry biomass and the suppression of giant ragweed, and can support grower decision‐making for timing of cereal rye termination.